Dental Caries and associated factors among 2-5 years children attending OPD of a selected Dental Hospital in Bangladesh - Md Asif Iqbal Khan; Md Mahfuzur Rahman; Md Mahfuz Hossain; Abu Syem Md Shahin (Update Dental College, 2013)
Background Despite remarkable reduction in the prevalence of dental caries in developed countries, dental caries is still a highly prevalent disease among children in developing countries. Objectives To estimate the oral health status of children under five years of age by assessing decayed, missing and filled teeth (dmft) status of primary teeth along with their tooth cleaning and food habits. Materials and Methods This cross-sectional study on oral health status of children under five years of age was carried out among 107 children attending the Outpatient Department of Sapporo Dental College and Hospital, situated at Uttara, Dhaka. Data was collected both in English and Bengali with a pre-tested structured questionnaire and a checklist. Results Dental caries (d) was found in 69.2% of the children while missing (m) and filled (f) teeth were recorded in 14% and 21.5% of the children respectively. Almost three quarter children (72%) demonstrated an overall dmft score 1 or higher; whereas one third children (28%) demonstrated dmft score 0 or free from any form of dental decay, missing teeth and dental filling. Increased age of the children was directly associated (p<0.05) with the number of decayed, missing or filled teeth. The study also revealed that correct method of brushing was practiced by only 44% of the children and recommended brushing time (1-3 minutes) was done by 37.3% only. Children who were assisted by their parents during brushing experienced less caries compared to the children who brushed their teeth by themselves and this finding was statistically significant (p<0.05). Taking snacks between meals was preferred by 106 children and among them 97.2% did not clean their mouth after having snacks. DOI: http://dx.doi.org/10.3329/updcj.v1i1.13945 Update Dent. Coll. j: 2011; 1 (1): 02-05